2004
DOI: 10.1080/1042819032000141275
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of CD38 Expression and its Quantification in B Cell Chronic Lymphocytic Leukemia (B-CLL)

Abstract: A large number of prognostic factors are available to help predict the outcome of patients who present with B-cell chronic lymphocytic leukemia (B-CLL). These include clinical stage, leukemic cell morphology, lymphocyte doubling time, the pattern of infiltration in bone marrow trephine biopsies, cytogenetic abnormalities, p53 function and serum factors such as beta-2 microglobulin. Two recently described major prognostic factors are immunoglobulin heavy chain variable region (IgVH) mutation status and cell mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…25 Likewise, SP cells from other mature B-cell malignant hemopathies, such as multiple myeloma, also present phenotypes inherent to the differentiation status of their non-malignant counterpart. 21 The increased level of CD38 expression, which here typified B-CLL SP cells from CD38 þ patients, is usually observed for highly proliferating B-CLL cells 29 and correlates with a poor clinical outcome, 30 supporting the view that B-CLL SP cells are important for progression of the disease. The fact that whether in vitro SP cells exposed to pertinent stimuli and microenvironmental cells 31 actually undergo more mitosis than the bulk of quiescent B-CLL cells remains elusive, although likely.…”
Section: Discussionmentioning
confidence: 72%
“…25 Likewise, SP cells from other mature B-cell malignant hemopathies, such as multiple myeloma, also present phenotypes inherent to the differentiation status of their non-malignant counterpart. 21 The increased level of CD38 expression, which here typified B-CLL SP cells from CD38 þ patients, is usually observed for highly proliferating B-CLL cells 29 and correlates with a poor clinical outcome, 30 supporting the view that B-CLL SP cells are important for progression of the disease. The fact that whether in vitro SP cells exposed to pertinent stimuli and microenvironmental cells 31 actually undergo more mitosis than the bulk of quiescent B-CLL cells remains elusive, although likely.…”
Section: Discussionmentioning
confidence: 72%
“…ZAP-70 and CD38 are independent prognostic factors in diagnosing patients with B-CLL [1,[3][4][5][6][17][18][19][20][21][22][23]. Hematogones have the potential to contribute misleading information to the evaluation of these two important prognostic markers if not excluded from the CLL population during the analysis of flow cytometric data.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 is a multifunctional ectoenzyme that exhibits NAD glycohydrolase, ADP ribosyl cyclase and ADP ribosyl hydrolase activities. A number of studies indicated that a high level of CD38 expression is a sign of malignancy (14,15). CD38 also has receptor activity in addition to its enzymatic features.…”
Section: Introductionmentioning
confidence: 99%